"Fak Germani": Materialities of Nationhood and Transgression in the Greek Crisis. (5th October 2015) - Kalantzis, Konstantinos
Abstract This essay explores Greek responses to the debt crisis, particularly middle-class Greeks and their current experiences of Greece's putative subordination to Germany in particular, and IMF and EU monitoring generally. I focus on the sphere of materiality and embodiment, while also exploring the role of desire and pleasure in Greeks' responses to their growing sense of subordination. Graffiti, popular protests, hip-hop expressive culture, and sexual joking are lenses through which I examine these themes. I also scrutinize my own positionality as a way of understanding the bitterness and ambiguity entailed in Greek reactions to the crisis. The essay illuminates how Greeks experience subjugation and respond to it through explosive resort to historical comparisons, sexual metaphors, and ill-mannered jokes.